Calypso & society in the Pre-Independence Trinidad - Rohlehr, Gordon (The author TunapunaTT, 1990)
Looks at calypso in relation to how society evolved in Trinidad. Focuses on factors such as immigration, multi-ethnicity, cultural confrontation, conflict and erosion, cultural formation, gender, class, humour, commercialism, ideological conflict, political development, tradition and change.